Mindfulness and its relationship with perceived stress, affect, and burnout in elite junior athletes - Gustafsson, H.; Davis, P.; Skoog, T.; Kentta, G.; Haberl, P. (Journal of Clinical Sport Psychology, 2015)
The purpose of this study was to examine the relationship between dispositional mindfulness and burnout and whether this relationship is mediated by perceived stress, negative affect, and positive affect in elite junior athletes. Participants were 233 (123 males and 107 females) adolescent athletes, ranging in age from 15-19 years (M = 17.50; SD = 1.08). Bivariate correlations revealed that mindfulness had a significant negative relationship with both perceived stress and burnout. To investigate mediation, we employed nonparametric bootstrapping analyses. These analyses indicated that positive affect fully mediated links between mindfulness and sport devaluation. Further, positive affect and negative affect partially mediated the relationships between mindfulness and physical/emotional exhaustion, as well as between mindfulness and reduced sense of accomplishment. The results point toward mindfulness being negatively related to burnout in athletes and highlight the role of positive affect. Future research should investigate the longitudinal effect of dispositional mindfulness on stress and burnout.